Application of Fractional Grey Forecasting Model in Economic Growth of the Group of Seven - Yumei Liao; Xu Wang; Jinrong Wang (Axioms, 2022)
This paper uses the idea of fractional order accumulation instead of the form of grey index, and applies the fractional order accumulation prediction model to the economic growth prediction of the member states of the Group of Seven from 1973 to 2016. By comparing different evaluation indexes such as <semantics>R2</semantics>, MAD and BIC, it is found that the prediction performance of fractional order cumulative grey prediction model (GM(<semantics>α</semantics>,1)) is significantly improved in the medium and long term compared with the traditional grey prediction model (GM(1,1)).